ANALISIS PERMAINAN TAPAK GUNUNG SEBAGAI MEDIA PENGEMBANGAN KEMAMPUAN NUMERASI YANG KONTEKSTUAL PADA ANAK USIA 4-5 TAHUN DI PAUD AISYIYAH BUSTANULATHFAL TANGERANG ELOK - Parmiyatun; Maya Lestari (LPPM IAD Probolinggo, 2026)
This study aims to analyze the use of the traditional game Tapak Gunung as a medium for developing contextual numeracy skills in children aged 4–5 years at PAUD Aisyiyah Bustanul Athfal Tangerang Elok. The study used a descriptive qualitative approach with a critical perspective. The research subjects consisted of 15 children in group A aged 4–5 years as well as teachers and the principal. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation. The results showed that the Tapak Gunung game modified with number symbols was able to stimulate children's numeracy skills, including number symbol recognition, counting skills, understanding number sequences, and simple pattern recognition. Most children showed an increase in numeracy skills through play activities involving physical movement and social interaction. From a critical perspective, the Tapak Gunung game not only functions as a medium for learning numeracy, but also as a means of preserving local culture and strengthening children's social values ​​amidst the dominance of digital games. Thus, the Tapak Gunung game can be used as an alternative contextual, fun, and meaningful learning medium in developing early childhood numeracy skills.